Exploration Process and Genesis Mechanism of Deep Geothermal Resources in the North Jiangsu Basin, East China: From Nothing to Something - Wang, Yibo; Bai, Yang; Wang, Lijuan; Guan, Junpeng; Wang, Yaqi; Wang, Zhuting; Hu, Jie; Hu, Shengbiao (Frontiers in Earth Science, 2021)
Geothermal resources have been recognized to be an important part of clean renewable energy, and the exploration, development, and utilization of geothermal resources, especially deep geothermal resources, are of great significance for achieving carbon peaking and carbon neutrality. Taking the North Jiangsu Basin (NJB) as an example, this paper reviews the exploration process of deep geothermal resources in the basin and presents the latest results with the latest data. The study shows that the NJB is a typical "hot basin" with an average heat flow value of 68 mW/m2; the deep geothermal resource favorable areas in the NJB are mainly distributed in the depressions, especially in the depressions near the Jianhu Uplift, not the Jianhu Uplift; the genetic mechanism of the deep geothermal resource favorable area in the NJB can be summarized as "two times, two sources" thermal concentration.